2p-6(p-8)=-(-7p-4)

Simple and best practice solution for 2p-6(p-8)=-(-7p-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2p-6(p-8)=-(-7p-4) equation:


2p-6(p-8)=-(-7p-4)

We simplify the equation to the form, which is simple to understand
2p-6(p-8)=-(-7p-4)

Reorder the terms in parentheses
2p+(-6p+48)=-(-7p-4)

Remove unnecessary parentheses
+2p-6p+48=-(-7p-4+)

Remove unnecessary parentheses
2p-6p+48=+7p+4

We move all terms containing p to the left and all other terms to the right.
+2p-6p-7p=+4-48

We simplify left and right side of the equation.
-11p=-44

We divide both sides of the equation by -11 to get p.
p=4

See similar equations:

| 5k-5=3k+10 | | 29.99+.45(750-500)=34.99+.40(750-500) | | 3(2x-8)=11x-18(x-3) | | 20y=15000 | | -4x+2=6x+22 | | 7-2m=25 | | 8(2k+3)-2(-7k+7)=70 | | 2*4.5= | | 2sin^3x+cos^2x=1 | | 2y-14=14x | | 8-6s=40 | | 6(2+6k)=-6(-7k-3) | | -(5x-1)+(2x+3)=17-(10x+1)+(x+6) | | 5*(x+3)-11=2x+19 | | x+38=2x+1 | | x^2-x-9xi-56-63i= | | f(5)=5-5 | | 17f+2=4f | | .5(8a+12)-27=15 | | p/8-1=7p/6+2 | | 40-2x=130-22x | | -3b+5b=2(2-b)+6(b-2) | | 4w+8=88 | | +2=7 | | (9x^4-6x^2+1)-(x^4-12x^3+34x^2+12x+1)=0 | | 2660+x(175.75)=5999.25 | | 72-x=86-2x | | -9+-5+14+-6= | | 5q+8=11 | | 2(3x+4y)=4x+2y | | 180-36-x=102 | | (13x-1)= |

Equations solver categories